The effect of cultural diversity challenges on organizational cynicism dimensions: A study from Egypt. Issue 3 (2nd July 2018) - Mousa, Mohamed
Abstract : Purpose: This paper aims to discover the effect of cultural diversity challenges (organizational communication, work- related discrimination and training) on physicians' cognitive, affective and behavioral cynicism in the context of public hospitals, Menoufia (Egypt). Design/methodology/approach: A total of 360 physicians at public hospitals in Menoufia (Egypt) were contacted and all of them received a set of questionnaires. After five follow ups, a total of 240 responses were collected with a response rate of 66.67 per cent. Findings: The findings suggest that only communication is considered the main and significant predictor for cognitive, affective and behavioral cynicism. Accordingly, when physicians perceive well-coordinated and balanced communication, they feel that their hospital has an adequate level of integrity and consequently will have a positive attitude toward it. Practical implications: Through well-formulated organizational communication, the hospital administration can decrease the organizational cynicism among physicians and subsequently their unwanted behavior. It is needless to say that when physicians experience an open-door communication climate, they experience a sense of psychological safety and give their very best. Originality/value: This paper contributes by filling a gap in management and organization literature, in which empirical studies on cultural diversity and organizational cynicism were limited until now.